Correlation Between Tooth Brushing Behavior And Oral Hygiene Status Among 18 To 54-Year-Olds - Utami, Sri; Herninda, Annisa Yumna; Dlya, Alyaa (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Plaque control by brushing teeth is essential to prevent dental diseases such as halitosis, dental caries, gingivitis, and periodontitis. The proportion of good daily tooth brushing behavior is not directly proportional to the proportion of dental and oral health problems, which is still high. Tooth brushing behavior which consists of time, frequency, duration, and method of brushing teeth, affects oral hygiene status. The aim of this study to determine the correlation between tooth brushing behavior and oral hygiene statusMethod: It is an observational study using a cross-sectional design. This study included 106 patients at RSGM UMY aged 18-54, which were selected using quota sampling. The variables of this study were tooth brushing behavior measured using a questionnaire, including frequency, duration, and time. Oral hygiene status was measured using the Oral Hygiene Index Simplified (OHIS). The data analysis used was Spearman's correlation test.Result: Spearman's correlation test revealed a significant correlation between brushing time (p=0.021, r=0.224), method (p=0.005, r=0.268), and frequency (p=0.000, r=0.372) to oral hygiene status. There was no correlation between tooth brushing duration (p=0,341) to oral hygiene status.Conclusion: There was a significant correlation between tooth brushing behavior, such as time, method and frequency of tooth brushing, to oral hygiene status.